Anti-Inflammatory, Antioxidant, and Antimicrobial Effects of Underutilized Fish Protein Hydrolysate. Issue 5 (28th May 2018) - Da Rocha, Meritaine; Alemán, Ailén; Baccan, Gyselle Chrystina; López-Caballero, M. Elvira; Gómez-Guillén, Carmen; Montero, Pilar; Prentice, Carlos
ABSTRACT: Antimicrobial, anti-inflammatory, and antioxidant activities of protein hydrolysates from Argentine croaker ( Umbrina canosai ) protein isolate (CPI) or Argentine croaker myofibrillar protein with different degrees of hydrolysis (DH: 10–20%) prepared using Alcalase or Protamex were determined. Results showed that an increase in the DH resulted in higher content of hydrophobic and aromatic amino acids (AAAs) and in a decrease in molecular weight (MW) distribution for all hydrolysates obtained. Furthermore, the enzyme and raw material used influenced the amino acid content and MW determined. Hydrolysates from CPI with a 20% DH by Alcalase had higher 2, 2ʹ-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) radical scavenging activity, metal chelation, and ferric-reducing antioxidant power ( p < 0.05). All hydrolysate samples decreased the pro-inflammatory capacity. In all the evaluated microorganisms, only seven were inhibited, most being Gram-positive. Alcalase was found to exert a considerable influence on antibacterial activity. These hydrolysates are an alternative as natural antimicrobials, anti-inflammatory, and antioxidant compounds.